Transabdominal approach laparoscopic ureteral reimplantation at the top of the bladder for the treatment of primary obstructive megaureter - Shang, Xianhui; Luo, Zhen; Li, Yingbo; Zhou, Guangxu; Mao, Yuchen; Tan, Hongyang; Mao, Kaiyi; Zhao, Peng; Wang, Cao; Jin, Zhu; Liu, Yuanmei (Frontiers in Pediatrics, 2025)
BackgroundCongenital primary obstructive megaureter (POM) is characterized by distal ureteral obstruction, leading to ureteral dilation, hydronephrosis, and potential renal impairment. Surgical intervention is necessary for severe hydronephrosis (SFU grade III–IV) or progressive renal decline. Open ureteral reimplantation is the standard treatment but is associated with significant surgical trauma and prolonged recovery. This study evaluates the safety and efficacy of transabdominal laparoscopic ureteral reimplantation (TALUR) at the posterior wall-bladder dome and compares its outcomes with the Politano procedure.MethodsThis retrospective, single-center study included pediatric POM patients who underwent ureteral reimplantation at the Affiliated Hospital of Zunyi Medical University from October 2019 to December 2023. Patients were assigned to the TALUR group (n = 21) or the Politano group (n = 20). Preoperative imaging, including renal ultrasound, magnetic resonance urography (MRU), and voiding cystourethrography (VCUG), confirmed the diagnosis. Primary endpoints included postoperative distal ureteral diameter, renal pelvic diameter, surgical success rate, perioperative complications, hospital stay, and vesicoureteral reflux (VUR) incidence. Follow-up assessments included ultrasound, MRU, and VCUG.ResultsAll procedures were successfully completed without conversion to open surgery. The TALUR group had a significantly shorter operative time (76.5 ± 12.6 min) compared to the Politano group (95.7 ± 14.8 min, P < 0.05). Postoperatively, distal ureteral diameter decreased from 14.6 ± 3.7 mm–4.8 ± 2.1 mm (P < 0.05), and renal pelvic dilation improved from 24.7 ± 5.3 mm–12.3 ± 2.6 mm (P < 0.05). The TALUR group had a shorter hospital stay (4.5 ± 0.5 vs. 6.1 ± 0.7 days, P < 0.05). Follow-up MRU showed improved ureteral patency and resolution of hydronephrosis. VCUG at six months showed mild VUR in two TALUR patients (9.5%) and one Politano patient (5.0%), all resolving within one year.ConclusionTALUR is a safe and effective minimally invasive technique for pediatric POM. Compared to the Politano procedure, TALUR offers shorter operative time, faster recovery, and comparable efficacy. Further large-scale studies are required to confirm its long-term effectiveness.